DETERMINANTS OF FIRM VALUE LISTED ON THE INDONESIAN STOCK EXCHANGE - Yeyen Ihsan Hidayat; Evi Gantyowati (JACTA: Journal of Accounting and Tax, 2025)
This study aims to examine the effect of tax avoidance, profitability, leverage and total sales on firm value in Indonesia. The data used is data from 97 companies listed on the Indonesia Stock Exchange in 2020-2022. This study uses panel data regression analysis. The best model chosen is the Fixed Effect Model (FEM). The results showed that partially tax avoidance and profitability have a significant positive effect on firm value, while leverage and total sales have no effect on firm value. Simultaneously, all the independent variables in this study have a significant effect on firm value. The implication of this research is that companies need to carry out tax avoidance optimisation strategies so that the company value continues to increase. Companies can also maximise production activities so that they can maximise profitability.